2019
DOI: 10.1186/s12969-019-0387-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and plaque microbial profile in juvenile idiopathic arthritis

Abstract: BackgroundThe oral microbiota has been implicated in the pathogenesis of rheumatoid arthritis through activation of mucosal immunity. This study tested for associations between oral health, microbial communities and juvenile idiopathic arthritis (JIA).MethodsA cross-sectional exploratory study of subjects aged 10–18 years with oligoarticular, extended oligoarticular and polyarticular JIA was conducted. Control groups included pediatric dental clinic patients and healthy volunteers. The primary aim was to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
6
13
0
2
Order By: Relevance
“…In line with our study, Grevich et al. found depletion of genera Prevotella (phylum Bacteroidetes) in JIA, but they report an overabundance of the genera Haemophilus and Kingella (phylum proteobacteria) in JIA, which was not found in our study ( Grevich et al., 2019 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our study, Grevich et al. found depletion of genera Prevotella (phylum Bacteroidetes) in JIA, but they report an overabundance of the genera Haemophilus and Kingella (phylum proteobacteria) in JIA, which was not found in our study ( Grevich et al., 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…The significantly higher gingival inflammation found in patients with JIA compared to healthy controls is in line with many studies investigating JIA and oral health ( Welbury et al., 2003 ; Ahmed et al., 2004 ; Leksell et al., 2008 ; Santos et al., 2015 ; Grevich et al., 2019 ). Other studies find no significant difference between JIA and healthy controls ( Miranda et al., 2003 ; Savioli et al., 2004 ; Reichert et al., 2006 ; Feres De Melo et al., 2014 ; Pugliese et al., 2016 ; Kobus et al., 2017 ; Maspero et al., 2017 ), probably depending on different study design and measurement indices of gingival inflammation ( Skeie et al., 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…Although Kingella species are mostly commensals of the oral cavity, they can cause human diseases such as Kingella kingae , which is described as a prime cause of invasive infections, including septic arthritis, osteomyelitis and spondylodiscitis in young children [ 5 ]. Grevich et al [ 6 ] reported that juvenile idiopathic arthritis patients had significantly more gingival inflammation, and plaque microbiota analysis revealed bacteria belonging to genera Kingella elevated. By contrast, other authors showed that periodontal inflammation, in case of gingivitis or periodontitis, was characterized by a reduction of Kingella species [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some genera, including Lautropia, Kingella, Neisseria, Actinomyces, Rothia and Megasphaera were extensively more abundant in the control samples. These genera have been associated with gingival health [15,34,67,[80][81][82][83]. Comparison of relative abundances of bacterial species revealed a substantially higher abundance of C. concisus in the two gingivitis groups versus controls (Figure 3).…”
Section: Discussionmentioning
confidence: 97%